Peer support programs in the fields of medicine and nursing: a systematic search and narrative review - Pereira, Lara; Radovic, Tamara; Haykal, Kay-Anne (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Peer-provided services exist in many different domains and professions. However, there is a knowledge gap in the existing programs’ descriptions and grouping that hinders creating new high-quality peer support programs. The objectives of this article are two-fold in describing existing peer support programs published in the literature in the medical field and evaluating their descriptive quality. Six electronic databases, grey literature, and reference lists were systematically searched. Studies reporting the existence of a support program delivered by peers and its description or methodology were included. Studies targeting patients and children were excluded. 11 articles were included in the qualitative synthesis and explored in detail. A total of 2155 peers participated in support programs in the fields of medicine, nursing, or both. Programs in other professional fields were not found. Programs were described in five different countries. Three methods of peer support delivery were found: in person, online, and mixed varying in their goals, duration, peer training supervision and participant demographics and number. Program descriptions were rated as good, fair, or poor using a verified rating scale.  There are numerous well-described programs varying in their methodology and type of delivery. Thus, the emergence of new programs can be based on such models that have been well-described in the literature.